Redesigning and Implementing the Public Game Information and Rating System in South Korea - HoSeong Kang; JungYoon Kim (Discrete Dynamics in Nature and Society)
Rating reviews in the game industry aim to enhance the protection of young users, promote game ethics, and prevent negative use of it as a gambling but recent studies and public opinions have reported that the current rating system in South Korea is excessively regulative. To address this issue, this study was conducted to redesign the public game rating system on the Game Ratings and Administration Committee (GRAC) for the public data usage based on the comparison with other better structured media rating systems. The redesigned system utilized a parsing technique to easily access specific data or items, and a Jsoup library was utilized in the Java environment. The system consists of a URL collection module, connection module, detailed collection module, and storage module. If a user requests information from a game rating database through the proposed system, the requested information is arranged sequentially and provided to the user in XML and JSON forms. The designed and implemented collection data were comparatively inclusive and structural to satisfy the public for the better and easier public data usage. This study is expected to help build an environment where game users can obtain information both easily and correctly, and it will eventually lead to a better understanding of the current game industry in South Korea and its clear way to go.